2023
DOI: 10.29309/tpmj/2023.30.02.7069
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of uropathogens in catheter associated urinary tract infections and their antimicrobial susceptibility.

Abstract: Objective: To assess the bacterial profile for catheter associated UTI and the antimicrobial sensitive to most  commonly used antibiotics in Sheikh Zayed Hospital, Rahim Yar Khan. Study Design: Cross-sectional study. Setting: Urology Ward of Sheikh Zayed Medical College/Hospital Rahim Yar Khan. Period: 01 February, 2021 to 31 July, 2021. Material & Methods: The urine samples were collected from 100 patients. Clinical and microbiological data were analyzed from patients with CAUTI. Results: A total of 100 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Other researchers reported similar results 6,26 . However, Hussain et al, 27 & Khan et al, 28 found that females have a stronger predilection for CAUTI compared to males due to the shorter female urethra that allows easier access of the perennial flora to the bladder along the catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers reported similar results 6,26 . However, Hussain et al, 27 & Khan et al, 28 found that females have a stronger predilection for CAUTI compared to males due to the shorter female urethra that allows easier access of the perennial flora to the bladder along the catheter.…”
Section: Discussionmentioning
confidence: 99%